Improving the physical qualities of volleyball players using aerobics at the stage of specialized basic training - Moshenska, T.; Petrov, D. (Slobozhanskyi herald of science and sport, 2020)
Purpose: theoretically develop and experimentally substantiate aerobic complexes to improve the physical qualities of volleyball players at the stage of specialized basic training.